Different grassland managements significantly change carbon fluxes in an alpine meadow - Xu, Ganjun; Kang, Xiaoming; Li, Wei; Li, Yong; Chai, Yongyu; Wu, Shengyi; Zhang, Xiaodong; Yan, Zhongqing; Kang, Enze; Yang, Ao; Niu, Yuechuan; Wang, Xiaodong; et al. (Frontiers in Plant Science, 2022)
Alpine meadow plays vital roles in regional animal husbandry and the ecological environment. However, different grassland managements affect the structure and function of the alpine meadow. In this study, we selected three typical grassland managements including free grazing, enclosure, and artificial grass planting and conducted a field survey to study the effects of grassland managements on carbon fluxes in an alpine meadow. The carbon fluxes were observed by static chamber and environmental factors including vegetation and soil characteristics were measured simultaneously. Our results show that the alpine meadow was a CO2 and CH4 sink, and grassland managements had a significant effect on all CO2 fluxes, including gross ecosystem production (GEP, P < 0.001), net ecosystem production (NEP, P < 0.001) and ecosystem respiration (ER, P < 0.001) but had no significant effect on CH4 fluxes (P > 0.05). The ranking of GEP under the different grassland managements was enclosure > free grazing > artificial grass planting. Furthermore, NEP and ER at enclosure plots were significantly higher than those of the free grazing and artificial grass planting plots. In addition, different grassland managements also affected the vegetation and soil characteristics of the alpine meadow. The aboveground biomass of artificial grass planting was significantly higher than that of the free grazing and enclosure plots. The vegetation coverage under three different grassland managements was ranked in the order of enclosure > artificial grass planting > free grazing and significant differences were observed among them. Moreover, significant differences in the number of species (P < 0.01) and the Margalef richness index (P < 0.05) were detected under three different grassland managements. Further analysis of the relationship between environmental factors and carbon fluxes revealed that GEP and NEP of the alpine meadow were positively correlated with vegetation coverage, the number of species, and the Margalef richness index. Therefore, grassland restoration should be configured with multiple species, which could improve carbon sink capacity while considering the functions of grassland restoration and production.